“Can we do it Next Year?” The Impact of the Flipped Classroom Method on EFL Learning Performance - Simona Kontrimienė; Rasa Raudienė; Raminta Čečetienė (Research in Language)
The flipped classroom (FC) method has been extensively adopted in STEM disciplines at the university level and garnered favorable results in synchronous learning, while less focus has been directed to its effectiveness in language teaching and learning at school. This experimental study aimed to explore how the flipped classroom approach affected EFL learning performance in the 6th grade. A 16-week semester-long flipped approach with pre-class materials and in-class interactive activities was implemented in two experimental and control EFL learner groups at a public general education school in Vilnius, Lithuania.